Finding Nemo - Disney; Walt (Rowville Funtastic Limited, 2006)
The story follows Marlin, a clownfish, who embarks on a daring journey across the ocean to find his son, Nemo, who has been captured by a diver. Along the way, Marlin is joined by Dory, a friendly but forgetful fish. Together, they face various underwater challenges and meet a host of colorful characters. The book captures the film$1 (Bs heartwarming themes of adventure, friendship, and perseverance, making it a fun and interactive way for children to experience the beloved story.s